The Development of E-Module with Blog Based in Basic Drawing of Software Engineering at Geomatics Competency - Mufid, Abdul; Supraptono, Eko; Kusumastuti, Adhi (Journal of Vocational and Career Education, 2021)
In Indonesia vocational high school (SMK) becomes one of the education levels that need to be developed. State vocational high school 1 Blora is a formal education that has many major competencies, one of them is geomatics engineering. Geomatics engineering is a major that carries out a series of learning activities covering various engineering subjects. In this field, the Basic Drawing of Software becomes crucial since it supports related subjects. E-module becomes one of the important requirements in the competency approach. These research aims are 1) developing the Autocad e-module; 2) Analyzing the worthiness e-module in Autocad; 3) Analyzing the practicality of the Autocad e-module to improve students’ competency in Basic Drawing of Software for Geomatics students. The current research applied Research and Development (RD) while feasibility and practicality validation analysis used intra-class correlation coefficients in SPSS v.25. The result of the study showed that an e-module with a blog based on the basic drawing was exclaimed very worthy based on material expert judgment with a 85,45 score. It is in line with the media expert who got a 86,43 score. The simplicity of the e-module was examined by geomatics engineering teachers and it achieved a 88,08 score. It can be concluded that this research is very worthy, simple, and very effective to improve geomatics students’ skills in Basic Drawing of Software.